Analysis the Effect of Digitalization and Technology on Web-Based Entrepreneurship - Budi Kurniawan Hutasuhut; Indah Purnama Sari; Al-Khowarizmi Al-Khowarizmi (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2023)
The development of technology is currently growing rapidly. Entrepreneurship and many technological advances are possible. The impact of technology on entrepreneurship has enormous advantages. By utilizing the internet network, technology has developed into a medium for business transactions, both products and services. Realize that the role of internet media can be used in the buying and selling process to increase sales turnover, as a way to market products to a wider market, and as a way to reduce operational costs such as store rental costs. This research on the impact of online website media on the buying and selling process is the main goal. in an effort to boost business at small retailers.